Estimating phosphorus delivery with its mitigation measures from soil to stream using fuzzy rules. (5th March 2013) - Zhang, T.; Page, T.; Heathwaite, L.; Beven, K.; Oliver, D. M.; Haygarth, P. M.
Abstract: To meet our environmental management responsibilities, there is a need to estimate the likely effect of current and future soil and land management policies on water quality and choose the most effective strategies given catchment characteristics, climate and economic drivers. Efficient management of diffuse phosphorus (P) delivery from agricultural soils to streams requires mitigation strategies to be modelled such that catchment mitigation strategies can be optimized. Owing to limited catchment‐scale experimental results upon which a mitigation measure rule‐base can be based, expert opinion was employed to make scale‐dependent extrapolations from the information available. Riparian buffer zone and wetlands are selected as two examples showing how the fuzzy rules are built. We discuss the challenges in the derivation and implementation of the fuzzy rules for the mitigation measures effectiveness such as, P trapping efficiency, up‐scaling process, catchment properties effect and the combination effect. The results demonstrated how effective each mitigation method could be for reducing the P delivery coefficient and that mitigation options should be selected according to catchment properties. This model can be applied for the evaluation of the effect of installed and to be installed mitigation measures on P delivery coefficient and give support for land management strategies.